Performance, Carcass Traits and Meat Quality of Lambs Fed with Increasing Levels of High-Oleic Sunflower Cake - Daviane M. Costa; Tharcilla I. R. C. Alvarenga; Isabela J. dos Santos; Paulo C. G. Dias Junior; Flavio A. P. Alvarenga; Nadja G. Alves; Iraides F. Furusho-Garcia (Agriculture)
The aim of this study was to evaluate the effect of sunflower cake from high-oleic seeds on performance, carcass characteristics, meat quality, and intramuscular fatty acid composition of finishing lambs. Thirty-six crossbred ewe lambs were assigned to four treatments (nine lambs/treatment) in a completely randomized design: 0 (control), 150, 300 and 450 g/kg DM of high-oleic sunflower cake. The lambs were weighed weekly and slaughtered with 42.3 ± 0.18 kg body weight and 270 ± 10.8 days of old. The inclusion of sunflower cake did not affect weight gain, dry matter intake and metabolizable energy intake (p > 0.05). There was an increase in neutral detergent fiber and EE intake (p < 0.01) with the inclusion of sunflower cake in the diet of the lambs. The inclusion of sunflower cake reduced hot and cold carcass yields (p < 0.01). Intramuscular fat content, L*, oleic acid, rumenic acid and EPA fatty acids linearly increased (p < 0.01) with the inclusion of high-oleic sunflower cake. The inclusion of high-oleic sunflower cake reduced saturated fatty acids (p < 0.01), except stearic acid, which linearly increased (p < 0.01). Up to 450 g/kg DM of high-oleic sunflower cake in the diet of lambs did not affect animal performance while providing a higher deposition of fat with better fatty acid composition for human consumption.